351 MULTIPLE PHARMACODYNAMIC ASSESSMENTS OF CANGRELOR EFFECTS IN ELECTIVE COMPLEX PCI: DATA FROM PHARMACODYNAMIC EFFECTS OF CANGRELOR IN PATIENTS WITH ACUTE OR CHRONIC CORONARY SYNDROME UNDERGOING PERCUTANEOUS CORONARY INTERVENTION REGISTRY. (15th December 2022) - Sperandeo, Luca; Marenna, Alessandra; Manzi, Lina; Avvedimento, Marisa; Simonetti, Fiorenzo; Canonico, Mario Enrico; Paolillo, Roberta; Spinelli, Alessandra; Borgia, Francesco; Di Serafino, Luigi; Franzone, Anna; Stabile, Eugenio; et al.
Abstract: Aims: Complex percutaneous coronary intervention (PCI) patients have greater risk of peri-procedural complications, with potential to be associated with poor short-term and late prognosis. Cangrelor is an intravenous P2Y12 receptor inhibitor characterized by rapid onset and offset effect of platelet inhibition which reduced the risk of thrombotic complications. Cangrelor use is currently approved in patients naïve from oral P2Y12 inhibitors with chronic (CCS) or acute coronary syndrome (ACS) undergoing PCI with a IIb recommendation by European guidelines. Yet, the process of switching from cangrelor to oral P2Y12 inhibitor remains uncertain. Methods and Results: POMPEII study (NCT04790032) is a prospective registry conducted at Federico II University of Naples enrolling all patients undergoing PCI and receiving cangrelor administration. Pharmacodynamic (PD) assessments were performed at baseline, at 30 minutes, 3 hours and 4-6 hours after cangrelor initiation with 3 assays: 1) the gold standard light transmittance aggregometry (LTA) (20- and 5-µM adenosine diphosphate [ADP] stimuli); 2) VerifyNow P2Y12-test; 3) Multiplate electrode aggregometry (MEA), ADP-test. We enrolled 41 patients undergoing elective complex PCI. All patients were P2Y12 inhibitor naïve and received aspirin, unfractionated heparin, and cangrelor (30-µg/kg bolus followed by 4-µg/kg/min infusion for 2 hours) prior to the start of PCI per standard of care. All patients showed low P2Y12 reactivity at 30 minutes during cangrelor infusion with a mean inhibition of platelet aggregation (IPA, %) of 55.7±18.0% at LTA 20-µM ADP test (34% with IPA ≤50%, 19.5% with IPA≥70%, 4.9% with IPA ≥80% and none IPA ≥90%). High residual platelet reactivity (HRPR) was observed in 1 case (2.4%) as shown by LTA (both 20- and 5-µM ADP stimuli) but not confirmed by VerifyNow and MEA. HRPR was observed in 55% at at 3h and 22.5% at 4-6h at LTA 20-µM and consistently with other assays. All patients with HRPR after cangrelor stop had received clopidogrel as switching drug, while no HRPR was observed in the 4 patients switching to ticagrelor. Conclusions: Cangrelor showed to be effective and safe in patients undergoing complex PCI at high thrombotic risk. The switch from cangrelor to clopidogrel could expose patients to a variable period of on-treatment HRPR with inadequate platelet inhibition probably due to the fast offset of cangrelor effect and delay of oral drug effect, while the use of ticagrelor soon after cangrelor start might be ideal to cover the gap. This might be of relevance in such a delicate clinical setting.